Knife edges technique for focused beam profiling of the photothermal imaging system - Amran, Azura; Saat, Nor Kamilah (Institute of Physics Publishing, 2018)
In this paper, we demonstrate knife edge techniques for measuring the focused beam profile of the photothermal imaging system. This quick and simple method of profiling the focused beam from Helium-Neon (He-Ne) laser is presented and detected by the PVDF thin film as a sensor. The study of focused beam profile is crucial so as to provide information of the focused beam such as beam resolution, depth of focus and the level of astigmatism of the beam. In knife edge technique, the blade moves across the beam in x and y-direction at varying axial position